News in brief - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2009)

(untitled)
Fist Represented at Asian Analysis X, Fist Represented at 57th Annual Congress Of Medicinal Plants And Natural Product Research, Central Analytical Lab facility update, Malaysian Natural Products International Seminar 2009